Response of Actinomycetes Inoculation to the Growth Rate of waxy Corn (Zea mays var. ceratina) - Adelia Salsabila Rahman; Novri Youla Kandowangko; Wirnangsih D. Uno; Yuliana Retnowati; Devi Bunga Pagalla; Hayatiningsih Gubali; Muhammad Isra; Aisyah Ahmad (Journal of Tropical Mycorrhiza, 2026)
Waxy corn (Zea mays var. ceratina) is an important food crop whose growth and productivity are strongly influenced by nutrient availability and soil microbial activity. The use of Actinomycetes as a biological biostimulant has gained attention due to its potential to enhance plant growth in an environmentally sustainable manner. This study aimed to evaluate the response of waxy corn growth rate to different doses of Actinomycetes inoculation. The experiment was conducted from July to December 2025 using a Randomized Block Design (RBD) consisting of three treatments: without Actinomycetes application (PA0), 5 g Actinomycetes (PA1), and 10 g Actinomycetes (PA2), with three replications for each treatment. Plant growth observations were performed at 14, 21, 28, 35, and 42 days after planting (DAP). Growth rate was determined based on the increase in plant dry biomass over each observation interval. The results showed that Actinomycetes inoculation affected the growth rate of waxy corn. The PA2 treatment consistently exhibited higher and more stable growth rates compared with PA0 and PA1 throughout the observation period. The enhanced growth performance was likely associated with the role of Actinomycetes in improving nutrient availability and stimulating vegetative development. In conclusion, the application of 10 g Actinomycetes demonstrated the greatest potential to increase the growth rate of waxy corn and may serve as an effective biological biostimulant for sustainable crop production.